2014
DOI: 10.1108/bij-09-2012-0064
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain performance measurement for third party logistics

Abstract: Purpose – The purpose of the paper is to explore the applicability of the Supply Chain Operations Reference (SCOR) model and to identify the key performance indicators (KPIs) for the service-oriented sector – namely a third-party logistics (3PL) service provider. Design/methodology/approach – The performance attributes of SCOR model (reliability, responsiveness, flexibility, cost measures and asset management efficiency) are used as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…The suggested framework for ESLPM process integration extends the existing limited research on environmental performance management frameworks and approaches (see frameworks by [14,15,17,23,26,27]). The framework adapts the process perspective from [13], for example, by including six ESLPM activities such as selecting variables, defining metrics, setting targets, measuring, feedback and analyzing the ESLPM process.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The suggested framework for ESLPM process integration extends the existing limited research on environmental performance management frameworks and approaches (see frameworks by [14,15,17,23,26,27]). The framework adapts the process perspective from [13], for example, by including six ESLPM activities such as selecting variables, defining metrics, setting targets, measuring, feedback and analyzing the ESLPM process.…”
Section: Discussionmentioning
confidence: 91%
“…This model possesses a challenge for an organization to define, align and prioritize the competitive requirements within each attribute [23]. Moreover, reference [26] argued that the SCOR model has been developed in a manufacturing context and is less available for service-based industries like 3PLs. Integration of environmental performance management process across organizations is also supported by guidelines for the phased implementation of an environmental management system ISO14005: 2010.…”
Section: Integrating Environmentally Sustainable Logistics Performancmentioning
confidence: 99%
“…Accordingly, in order to identify the key indicators in logistics performance measurement, the Balanced Scorecard (BSC) concept, which is a widely accepted approach (Rajesh et al, 2012), was found to be suitable for the present study due to its outstanding features, such as incorporating financial and non-financial indicators from different perspectives (Jothimani & Sarmah, 2014;PovedaBautista et al, 2012;Chia, Goh, & Hum, 2009) and allowing cause-and-effect relationships (Kaplan & Norton, 1996). Thus, the present study extends the existing knowledge on the applicability of the BSC in the logistics industry by presenting a comprehensive balanced set of logistics performance indicators from different perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…The Supply Chain Operations Reference (SCOR) is a model that supports the development of the Performance Measurement System (PMS). SCOR function is not only to measure and improve the internal and external business processes of the company [28], but also displays a crossfunctional framework that links business processes measurement of techniques, guidelines, and performance [29]. The SCOR model, perfect order fulfilment and overall value at risk, have been used to measure supply chains for material construction to support sustainable construction [30], as well as to measure supply chain performance in building projects [31].…”
Section: Supply Chain Operation Reference (Scor) Modelmentioning
confidence: 99%